Marketing Practices of a Private Higher Education Institution in the Philippines - Jojie R. De Ramos; Jesus P. Briones (International Journal of Marketing and Digital Creative, 2024)
In the competitive landscape of higher education, effective marketing practices are essential for institutions aiming to enhance student satisfaction, attract and retain students and secure long-term sustainability. This study evaluated the marketing practices of a private higher education institution in the Philippines, focusing on the perspectives of its personnel and students. Using the Segmentation, Targeting, and Positioning (STP) model, the research assessed various areas of marketing practices, such as target markets, marketing goals, promotions, and marketing initiatives. Using descriptive-quantitative design utilizing a researcher-structured questionnaire, the study involved a sample of 140 students and 22 personnel. The findings highlight a moderate extent of effective market targeting, strategic alignment of marketing goals and promotions, and relevant employment of marketing initiatives, with the perceptions of personnel and students having no significant differences. Key areas identified for improvement include enhancing personalized marketing approaches, strengthening integrated planning and communication, and refining promotional efforts to better align with students’ needs and expectations. Based on these findings, the study suggests comprehensive marketing strategies to improve current practices. This provides actionable insights for educational institutions seeking to optimize their marketing strategies in a rapidly evolving educational environment.